Occupational asthma in a coal miner. - Gamboa, P. M. (1996)
Occupational asthma in coal miners is hardly recognised. A report is presented of a coal miner whose clinical picture suggested a respiratory allergy which occurred only in the mine where he worked. Serum specific IgE levels, skin tests, and bronchial provocation tests with different commercial extracts showed sensitisation to Rhizopus nigricans. Rhizopus spp were found inside the mine, as demonstrated by cultures on petri plates.